Treatment of pediatric COVID on outpatient basis - Weling, Rajaram M. (International Journal of Contemporary Pediatrics, 2022)
Background: Since December 2019, coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has rapidly spread, becoming the first pandemic of the 21st century by number of deaths (over 3.8 million deaths worldwide) and still increasing. Many aspects of SARS-CoV-2 infection in children and adolescents remain unclear, and optimal treatment has not yet been defined. Methods: This is a collective descriptive study with analytical wing; on 756 children who were COVID-19 positive; at Ameya well baby clinic at Ameya orthopaedic centre and children hospital, Borivali West, Mumbai, India from December 2019 up to December 2021. In our study 756 children from birth to fifteen years who were symptomatic for COVID-19 and the diagnosis was confirmed by COVID RTPCR positive test, were treated with our standard protocol which included nebulization, bronchodilators and antibiotics on outpatient basis, with home quarantine and follow up done by teleconsultation. Data was entered and analysed using SPSS software version 11. Proportions were compared using Chi square (χ2) test of significance, categorical variables were assessed using χ2. In all the above the p value of less than 0.05 was accepted as indicating statistical significance. Results: In the study the covid affected children were treated with our protocol improved (p value less than 0.05). Conclusions: The findings of this study clearly establish the role of our protocol in treating COVID affected children on out-patient basis in the current COVID scenario prevailing in our country.